ChartVision: Accessible Vertical Bar Charts - de Oliveira, Cynthya Letícia Teles; Silva, Alan Trindade de Almeida; de Morais, Jefferson Magalhães; Mota, Marcelle Pereira (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2020)
People with different visual impairments interact with the technology using specific tools ranging from appropriate software, increasing the contrast of the elements, and screen readers using a synthesized voice. In this context, it is crucial to make charts that could be expressed by existing technologies. In the literature, we can find charts descriptions manually done, which is not easily scalable and may have an interpretation bias. Considering a scenario where data are automatically extracted from charts available anywhere using computational vision or other techniques, we propose using templates to describe simple and grouped vertical bar charts. This work presents some description templates and a prototype tool that aims to make accessible bar charts. We performed several tests to validate the proposed templates and the prototype, which is an application for mobile devices. Results show directions about the description templates use and demonstrate their feasibility in a computational tool.